155k views
3 votes
As tabelas abaixo mostram algumas entradas e saídas das funções feg. T -6 -3 0 3 6 9 f(2 0 2 4 6 8 10 20 --6 -3 0 2 4 5 g(x) 75 30 3 -5 -5 -2 (gof)(-6)=

As tabelas abaixo mostram algumas entradas e saídas das funções feg. T -6 -3 0 3 6 9 f-example-1
User MD Zand
by
5.1k points

1 Answer

4 votes

To determind gof(-6) first determine f(-6).

From the table,


f(-6)=0

Now gof(-6) can be determined as,


\begin{gathered} \text{gof}(-6)=g(f(-6)) \\ =g(0) \\ =3 \end{gathered}

Thus, the required solution is 3.

User Suresh Murali
by
5.2k points